2013
DOI: 10.1002/chem.201202833
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Thermal‐ and Photostable Titania with Paramagnetic Oxygen Vacancies for Visible‐Light Photocatalysis

Abstract: A novel dopant-free TiO(2) photocatalyst (V(o)(.)-TiO(2)), which is self-modified by a large number of paramagnetic (single-electron-trapped) oxygen vacancies, was prepared by calcining a mixture of a porous amorphous TiO(2) precursor, imidazole, and hydrochloric acid at elevated temperature (450 °C) in air. Control experiments demonstrate that the porous TiO(2) precursor, imidazole, and hydrochloric acid are all necessary for the formation of V(o)(.)-TiO(2). Although the synthesis of V(o)(.)-TiO(2) originates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
127
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(136 citation statements)
references
References 57 publications
7
127
1
1
Order By: Relevance
“…Raman spectroscopy (Figure 5c) reveals that the strongest vibration mode area (Eg) at 144 The EPR technique was further employed to analyze the Ti 3+ -related vacancy defects. From Figure 5b, there is an obvious signal at g = 2.058 for the g-anatase sample, which can be attributed to oxygen vacancy [30]; therefore, the defects probed from slow negative annihilation spectroscopy may be considered to be oxygen-related vacancy, which is consistent with the XPS results. Oxygen-related vacancy defects mainly exist in the bulk (or surface) lattice of the TiO 2 samples after reduction treatment.…”
Section: Characterization Of Colored Anatasesupporting
confidence: 79%
See 1 more Smart Citation
“…Raman spectroscopy (Figure 5c) reveals that the strongest vibration mode area (Eg) at 144 The EPR technique was further employed to analyze the Ti 3+ -related vacancy defects. From Figure 5b, there is an obvious signal at g = 2.058 for the g-anatase sample, which can be attributed to oxygen vacancy [30]; therefore, the defects probed from slow negative annihilation spectroscopy may be considered to be oxygen-related vacancy, which is consistent with the XPS results. Oxygen-related vacancy defects mainly exist in the bulk (or surface) lattice of the TiO 2 samples after reduction treatment.…”
Section: Characterization Of Colored Anatasesupporting
confidence: 79%
“…Raman spectroscopy (Figure 5c) reveals that the strongest vibration mode area (Eg) at 144 cm −1 had a significant peak broadening and blue shifting after reduction treatment, compared with commercial anatase. The peak broadening effect and shift have been observed in several recent studies on hydrogenated TiO 2 [22,[30][31][32], which are attributed to the presence of lattice disorder resulting from phonon confinement or nonstoichiometry as the result of oxygen vacancy (VO) doping.…”
Section: Characterization Of Colored Anatasementioning
confidence: 99%
“…2(b). The absorption of visible light may be attributed to the existence of Ti 3+ and oxygen vacancy [11][12][13][14][15][16][17]31]. Zuo et al found that Ti 3 + generated from the reduction of Ti 4+ by H 2 produced from the reaction between Ti powder and HCl solution could induce a vacancy band of electronic states right below the conduction band, which narrows the band gap [11].…”
Section: Characterization Of Photocatalystsmentioning
confidence: 96%
“…Rapid recombination of charge carriers (i.e., electron and hole) drastically reduces the solar energy conversion efficiency. Recently, self-modification of the atomic structures by removing or reconstructing atoms has been demonstrated as an effective method to extend the absorption spectra of photocatalysts, while significantly alleviating electron-hole recombination [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. For example, self-modified TiO 2 displayed satisfactory performance for visible light photocatalytic H 2 O reduction to hydrogen [9,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 96%
“…), which is consistent with the reported result. [30] Sample Ag-P25 with the same Ag and Ti molar ratio as AT-20 was investigated and shows an H 2 production activity of 36.8 mmol h the samples are stable that produce H 2 during the time evolution. These results illustrate the clear promotion of heterojunction Ag-TiO 2 nanopillars for the following reasons: 1) the junctions between Ag and TiO 2 are propitious to charge separation, which promotes the photocatalytic activity; 2) the surface plasmon resonance effect of Ag can utilize much visible light; and 3) the one-dimensional structure favors charge transport.…”
mentioning
confidence: 99%